Kết luận Phiên giải trình về "Việc thực hiện một số quy định của pháp luật về hoạt động công chứng" - Ủy ban Pháp luật (2023)
Toàn văn Kết luận Phiên giải trình về "Việc thực hiện một số quy định của pháp luật về hoạt động công chứng".